Історично-педагогічні передумови становлення загальної гуманітарної підготовки студентів у вищій школі США - Світлана Федоренко (Pavlo Tychyna Uman State Pedagogical University, 2015)
На основі теоретичного аналізу праць американських дослідників та освітніх документів представлено авторську періодизацію основоположних напрямів становлення загальної гуманітарної підготовки студентів у США. Виокремлені п'ять основних періодів розвитку загальної гуманітарної складової американської вищої освіти схарактеризовано з позицій змісту та структури навчальних куррикулумів, а також організації навчально-виховного процесу в американських закладах вищої освіти з моменту заснування її перших інституцій на теренах США. Встановлено, що початок ХХІ століття ознаменувався появою нової, удосконаленої моделі загальної гуманітарної освіти у вищій школі США, яка по праву може називатися суто американською на противагу класичній англосаксонській моделі, з якої вона бере свої витоки. На основе теоретического анализа работ американских исследователей и образовательных документов представлена авторская периодизация основных направлений становления общей гуманитарной подготовки студентов в США. Выделены пять основных периодов развития общей гуманитарной составляющей американского высшего образования охарактеризованы с позиций содержания и структуры учебных куррикулумов, а также организации учебно-воспитательного процесса в американской высшей школе с момента основания ее первых институтов на территории США. Установлено, что начало XXI века ознаменовалось появлением новой, усовершенствованной модели общего гуманитарного образования в высшей школе США, которая по праву может называться чисто американской в противовес классической англосаксонской модели, с которой она берет свои истоки. The paper highlights the historical roots of liberal arts education (it is also known as general education), tracing its development through five singled periods. In early American higher education there was a unified liberal arts curriculum focused largely on classical studies. Over time, a new emphasis on education as a means to prepare individuals for a variety of vocations caused modifications in how general education has been offered to students. Nowadays it is something of an educational industry in the United States as nowhere else in the world. As the twenty-first century begins, liberal arts education has become a part of every student's baccalaureate education and should be viewed as a method of enhancing the overall level of learning for undergraduate students. Liberal arts education is a modern conceptualization of an old idea. It is therefore an essential and critical piece of the overall undergraduate educational experience. Liberal arts education is tightly correlated with the values of American democracy, with American ideas of citizenship, and with American view of a life well lived. This type of undergraduate study has worked out the ideal of liberally educated student of the twenty-first century who is a lifelong learner, open-minded, tolerant, intellectually curious, self-actualizing with striving for personal growth, physical and mental health and spiritual well-being. As a learner and global citizen, the liberally educated person is actively engaged with the world in all of its complexity, diversity and dynamism. Liberal arts education in the US higher school continues to be reviewed and reevaluated historically and philosophically, and its models continue to be reexamined and restructured.